Barriers and facilitators to providing primary care-based weight management services in a patient centered medical home for Veterans: a qualitative study. Issue 1 (December 2015) - Jay, Melanie; Chintapalli, Sumana; Squires, Allison; Mateo, Katrina; Sherman, Scott; Kalet, Adina
Abstract Background Obesity is highly prevalent among Veterans. In the United States, the Veterans Health Administration (VHA) offers a comprehensive weight management program called MOVE!. Yet, fewer than 10 % of eligible patients ever attend one MOVE! visit. The VHA has a patient-centered medical home (PCMH) model of primary care (PC) called Patient-Aligned Care Teams (PACT) at all Veterans Affairs (VA) Medical Centers. PACT teamlets conduct obesity screening, weight management counseling, and refer to MOVE!. As part of a needs assessment to improve delivery of weight management services, the purpose of this study was to assess PACT teamlet and MOVE! staff: 1) current attitudes and perceptions regarding obesity care; 2) obesity-related counseling practices 3) experiences with the MOVE! program; and 4) targets for interventions to improve implementation of obesity care in the PC setting. Methods We recruited 25 PACT teamlet members from a single VA study site—11 PC physicians, 5 registered nurses, 5 licensed practical nurses, 1 clerical assistant, and 3 MOVE! staff (2 dietitians, 1 psychologist)—for individual interviews using a combination of convenience and snowball sampling. Audio recorded interviews were professionally transcribed and iteratively coded by two independent reviewers. The analytic process was guided by discourse analysis in order to discover how the participants perceived and provided weight management care and what specific attitudes affected their practices, all as bounded within the organization. Results Emerging themes included: 1) role perceptions, 2) anticipated outcomes of weight management counseling and programs, and 3) communication and information dissemination. Perceived role among PCPs was influenced by training, whereas personal experience with their own weight management impacted role perception among LPNs/RNs. Attitudes about whether or not they could impact patients' weight outcomes via counseling or referral to MOVE! varied. System-level communication about VHA priorities through electronic health records and time allocation influenced teams to prioritize referral to MOVE! over weight management counseling. Conclusion We found a diversity of attitudes, and practices within PACT, and identified factors that can enhance the MOVE! program and inform interventions to improve weight management within primary care. Although findings are site-specific, many are supported in the literature and applicable to other VA and non-VA sites with PCMH models of care.